Perinatal interventions to reduce the severity of postpartum depression: A narrative review - Rosyidah, Hanifatur; Nakatudde, Hadijah; Adyania, Kartika; Susanti, Siti (Universitas Aisyiyah Yogyakarta, 2023)
Postpartum depression (PPD) is a mental disorder that can affect mothers and their families, with symptoms of fatigue, mood swings, frequent anger for no reason, and excessive worry for the baby. Several studies regarding interventions that can be given to postpartum women with PPD have been carried out. The purpose of this review is to assess evidence on the effectiveness of a broad range of perinatal interventions to reduce the severity of PPD. The review of the literature has been done through PubMed, for papers with Randomized Control Trial (RCT) design published in 2012-2021. The approach was to explore quantitative parameters which is the EPDS score. More than 300 papers were identified, but only 6 studies met the inclusion criteria. A narrative review was conducted due to the studies' significant heterogeneity. Six studies reported a decrease in EPDS score. Six interventions have been identified to reduce the severity of PPD, they are exercise, psychological intervention, telephone-based Cognitive Behavioral Therapy (CBT), iBA (internet Behavioral Activation), application-based Cognitive Behavioral Therapy (CBT) and psychoeducation. This review suggests that multiple intervention program may lead to better outcomes in terms of client’s satisfaction. There is also some indication that psychoeducation support Maternal Parental Self-efficacy (MPSE) and social support besides EPDS.